Hubungan Motivasi Kerja dan Dukungan Sosial Kepala Sekolah dengan Pelaksanaan Tugas Guru Bk di SMPN Kab. Kerinci - Rahmawati, Rahmawati; Neviyarni, Neviyarni; Firman, Firman (Konselor, 2014)
The counselor job and responbility is to give guidance and counseling service, performing the job needs motivation in order to reach the educational purpose. The headmaster is responsible to provide the facilities for the counselor in doing them job. The purpose of the study is to find out the relationships between the headmaster’s working motivation and social support with counselor performance. This research used quantitative in nature, using correlation method. Objective of the Research be done counselor in Junior high school Kerinci. The results of the study revealed that, there is a significant relationship between the headmaster’s working motivation and social support with the counselor performance.